2023
DOI: 10.1002/app.53692
|View full text |Cite
|
Sign up to set email alerts
|

Visible light‐catalyzed living cationic homopolymerization and copolymerization of isobutyl vinyl ether: Characteristics and mechanism

Abstract: On the basis of synthesizing a highly efficient chain‐transfer agent ethyl (1‐isobutoxyethyl) carbonotrithioate(CTA), living cationic polymerization of isobutyl vinyl ether (IBVE) was successfully initiated by visible light catalysis. The random copolymerization of isobutyl vinyl ether and propyl vinyl ether (PVE), cyclohexyl vinyl ether (CyVE), and 2‐chloroethyl vinyl ether (CEVE) was achieved on the basis of investigating the reactivity ratios of vinyl ether monomers. The influence of photocatalyst (PC) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Our findings showed that high photocatalyst (PC) concentrations and blue LED wavelengths were optimal for this reaction system. 172 With the advancements in reactive cationic and lightcontrolled polymerization, cationic RAFT polymerization has gained considerable attention in conventional systems, drawing inspiration from photoinitiated cationic RAFT polymerization. [173][174][175][176][177][178] The control degree during polymerization has significantly improved, especially in photoinitiated polymerization where chain growth is directly regulated by light.…”
Section: Photocontrolled Cationic Polymerizationmentioning
confidence: 99%
“…Our findings showed that high photocatalyst (PC) concentrations and blue LED wavelengths were optimal for this reaction system. 172 With the advancements in reactive cationic and lightcontrolled polymerization, cationic RAFT polymerization has gained considerable attention in conventional systems, drawing inspiration from photoinitiated cationic RAFT polymerization. [173][174][175][176][177][178] The control degree during polymerization has significantly improved, especially in photoinitiated polymerization where chain growth is directly regulated by light.…”
Section: Photocontrolled Cationic Polymerizationmentioning
confidence: 99%